2013
DOI: 10.1021/jp4058516
|View full text |Cite
|
Sign up to set email alerts
|

The Badger–Bauer Rule Revisited: Correlation of Proper Blue Frequency Shifts in the OC Hydrogen Acceptor with Morphed Hydrogen Bond Dissociation Energies in OC–HX (X = F, Cl, Br, I, CN, CCH)

Abstract: Potential morphing has been applied to the investigation of proper blue frequency shifts, Δν0 in CO, the hydrogen acceptor complexing in the hydrogen bonded series OC-HX (X= F, Cl, Br, I, CN, CCH). Linear correlations of morphed hydrogen bonded ground dissociation energies D0 with experimentally determined Δν0 free from matrix and solvent effects demonstrate consistency with original tenets of the Badger-Bauer rule (J. Chem. Phys. 1937, 5, 839-51). A model is developed that provides a basis for explaining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Prediction of D 0 for OC-H 2 O was estimated to be 355(13) cm -1 bases on applications of potential morphing to the Badger-Bauer rule [26]. As show in Table XIV…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of D 0 for OC-H 2 O was estimated to be 355(13) cm -1 bases on applications of potential morphing to the Badger-Bauer rule [26]. As show in Table XIV…”
Section: Resultsmentioning
confidence: 99%
“…In the current work, we shall develop algorithms for the 5-D and 6-D morphed potentials for OC-H 2 O. These model results will be compared with the previously available spectroscopic data and also used to make predictions of the rovibrational data for the intermolecular vibrations based on the current available spectroscopic analyses and an accurate estimate of the ground state dissociation energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation energy of N 2 -H 2 O has not been experimentally determined though it is expected to be approximately half that of OC-H 2 O. The latter is known [26] to have D 0 = 355(13) cm −1 with well resolved rovibrational substructure [27] in its bending vibration, so it is expected that the predissociative line broadening should be significantly less than that in H 2 O dimer which is what is observed for N 2 -H 2 O in Figure 2. The current rovibrational analysis is valuable for generation of accurate rovibrational spectroscopic data for the potential energy surface of N 2 -H 2 O and assessing of quantum chemical calculations used to evaluate intensities of vibrations as a function of temperature on the quantitation of N 2 -H 2 O continuum [4].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, perhaps the earliest is the Badger–Bauer rule that correlates the redshift in the donor stretching frequency with the enthalpy of hydrogen‐bond formation . Examples that follow the Badger–Bauer rule have been reported in the literature …”
Section: Introductionmentioning
confidence: 93%
“…[16] Examples that follow the Badger-Bauer rule have been reported in the literature. [17][18][19][20][21] In ar ecent report, our group demonstrated that for as eries of CÀH···X (X = O, N) hydrogen-bonded complexes of 3-fluoro-phenylacetylene and 2,6-difluorophenylacetylene the redshifts in the CÀHs tretchingf requency weren ot linearly correlated with the stabilization energies. [22] Analysis of the frequency shifts with the aid of symmetry-adaptedp erturbation theory (SAPT), which separates the total interaction energy into physically well-defined components, such as electrostatics, induction, dispersion, and exchange repulsion, suggested that the redshifts in the donors tretchingf requency are linearly proportional tot he electrostaticc omponent of the total stabilization energy.S imilar results were reported for the water complexes of various substituted phenolsi nvestigated by using matrixisolation spectroscopy.…”
Section: Introductionmentioning
confidence: 99%